(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article contains information about the fact that cotton plants control many physiological functions due to their large leaf surface area. Among them, it is important for such indicators as photosynthesis rate, net photosynthetic productivity, and leaf water evaporation. The leaf surface area of ​​cotton plants in the tillering phase in the control variant without fertilizer was 252.9 cm2. In the variant with N250, P175, K125 kg recommended in the experiment, it was 346.3 cm2, which was the best result in this phase among all salinity levels